UPAYA GURU BK MENGATASI PERILAKU AGRESIF MELALUI LAYANAN KONSELING PERORANGAN DI KELAS X SMA KARIKA I-5 PADANG - Nurhasnah, Nurhasnah (Bimbingan dan Konseling, 2014)
This research of background by existence of  aggresive behavioral educative participant in school and how effort counselor in overcoming the problem of aggresive behavioral educative participant. Purpose of this research is to know: (1) aggresive behavioral form which overcome pass service of counseling individual, (2)effort counselor overcome aggresive behavior in service of counseling individual at construction phase. This research pass descriptive approach qualitative. Instrument which researcher use in this research is interview, technique which used in data processing is data discount, displayed by data, with drawal of conclusion, improving authenticity of result, and narasi result of analysis. Result of research the obtained is: (1) aggresive behavioral Form which overcome pass service of counseling individual like: quarreling, beating, pinching, fight against, abusing. (2) Effort counselor overcome aggresive behavior in service of counseling individual at construction phase, that is: service of counseling individual which executed to be focussed to educative participant freshment for openness and voluntary in course of counseling, used technique like my practice hold responsible and gift of advise, besides also give and praise of  responsibility to change and apply regulation of school, and work along with personnel go to school and old fellow to control aggresive behavior of educative participant.